Hard Skills, Soft Skills, and Productivity: Determinants of Income Improvement Among Vocational Training Graduates - Makmuri Ahdi; Fahru Ravi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study expands the understanding of the impact of hard skills, soft skills, and vocational training by moving beyond a narrow focus on technical abilities to include psychological and social dimensions while exploring the long-term effects on alumni income. It specifically aims to analyze how hard skills, soft skills, and vocational productivity training influence the income growth of alumni from the Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Bekasi. Utilizing a quantitative methodology, the research draws from primary data collected via questionnaires and secondary data from supporting documentation. The study population consists of all 2024 trainees who completed programs at Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Bekasi, with sampling determined by the Slovin formula. Partial data analysis was conducted using t-tests, revealing that hard skills significantly affect income growth with a calculated t-value of 4.600, exceeding the t-table value of 1.985. Similarly, soft skills partially influence income increases with a t-value of 5.901 against the 1.985 threshold, and vocational productivity training also shows a significant partial impact with a t-value of 3.893 compared to the t-table value of 1.985.